2003
DOI: 10.1021/nl0340531
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically-Driven Self-Assembly:  A Geometric Packing Analysis

Abstract: We present a new approach to the problem of finding the minimum-energy structures resulting from the self-assembly of amphiphile nanoparticles possessing a hydrophobic "tail" and a hydrophilic "head". When the repulsive interactions between the "heads" are of hard-sphere type, the approach is rigorous and is reduced to a simple geometric problem of finding the highest density structure allowed by the nanoparticle shape. Our results show that spherical micelles always have higher fractional density for cone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 4 publications
8
71
0
1
Order By: Relevance
“…The approximately spherical shape of these larger clusters is consistent with the theoretical prediction of Tsonchev et al (14) that spherical structures are preferred in the limit of large N. The absence of cylindrical clusters is likely due to the hard-core repulsive interactions between cones, which is equivalent to a cone-cone interaction of effectively high bending energy. According to continuum theory (28), spherical structures are energetically preferred for high ratios of bending energy to stretching energy.…”
Section: Self-assembly Of Cones and Spherical Particles (Moderate To supporting
confidence: 88%
“…The approximately spherical shape of these larger clusters is consistent with the theoretical prediction of Tsonchev et al (14) that spherical structures are preferred in the limit of large N. The absence of cylindrical clusters is likely due to the hard-core repulsive interactions between cones, which is equivalent to a cone-cone interaction of effectively high bending energy. According to continuum theory (28), spherical structures are energetically preferred for high ratios of bending energy to stretching energy.…”
Section: Self-assembly Of Cones and Spherical Particles (Moderate To supporting
confidence: 88%
“…We will assume that the cones have flat bases with the opening angle ␣ at their apex and the slant height L. In micelles (20), the solvent induces a tip-to-tip attraction between the cones. Here, we consider the role of base-to-base stacking in facilitating planar packing.…”
Section: Resultsmentioning
confidence: 99%
“…For a cylindrical micelle, the number of cones in an elementary cell, defined as a cylinder section of thickness L sin(␣/2) ͌ 3 (20), is N c ϭ [2 /␣], and the volume of such an elementary cell is V cell cyl ϭ L 3 sin(␣/2) ͌ 3. The packing fraction of cylinders in a hexagonal arrangement is /(2 ͌ 3).…”
Section: [3]mentioning
confidence: 99%
“…The formation of b-sheets blocks the formation of alternative aggregates, such as spherical micelles or layered structures even when molecules vary greatly in their shapes. Tsonchev et al (2003Tsonchev et al ( , 2004 showed through calculations and Monte Carlo simulations that spherical micelles are preferred by tapered molecules. Israelachvili et al (1976) has postulated that surfactants will aggregate into spheres, cylinders or layered assemblies depending on how tapered is the shape of molecules.…”
Section: One-dimensional Assembliesmentioning
confidence: 99%